Cover Feature: Stable and Persistent Acyclic Diaminocarbenes with Cycloalkyl Substituents and Their Transformation to β‐Lactams by Uncatalysed Carbonylation with CO (Chem. Eur. J. 6/2019). Issue 6 (16th January 2019) - Wallbaum, Lars; Weismann, Daniel; Löber, Dennis; Bruhn, Clemens; Prochnow, Pascal; Bandow, Julia E.; Siemeling, Ulrich
Abstract : Acyclic diaminocarbenes (ADACs) are ambiphilic, which makes them suitable for the activation of fundamentally important small molecules. For example, most of them react with CO under mild conditions. Unfortunately, such high reactivity is accompanied by limited thermal stability, leading to their decomposition at room temperature or below. The new ADAC [( cyclo ‐C6 H11 )2 N]2 C is stable in solution up to approximately 40 °C. Nevertheless, it reacts readily with CO. The carbonylation affords a β‐lactam derivative with useful antibiotic properties. More information can be found in the Full Paper by U. Siemeling et al. onpage 1488 .